Uncertainty premia in REIT returns - Marton Lotz; Daniel Ruf; Johannes Strobel (Real Estate Economics, 2023)
We provide a systematic study of how financial and real estate uncertainty affect the aggregate return performance of the U.S. REIT market from 1994 to 2017. A temporal causality analysis reveals a negative uncertainty impact on REIT returns. The asset pricing analysis confirms the predictive relation and suggests that REITs are statistically significantly exposed to changes in market-wide uncertainty, for which investors require a return compensation. We also identify economic state variables to explain time-varying uncertainty exposures as well as periodic hedging characteristics of REITs. Finally, we find evidence that the source of uncertainty matters for compensating expected REIT~returns.
Keywords: 330; asset pricing; REITs; uncertainty